Drinking Water in the United States: Are We Planning For a Sustainable Future? - Derrington, Erin (Consilience, 2011)
Maintaining drinking water quality and quantity is a resource management challenge worldwide. In the United States, there are federal, state and local laws to further drinking water quality protection, but few regulations that address water quantity. The first part of this article summarizes existing water protection laws, especially the division of water quality protection and local land use regulation between federal and state government. The second part assesses current water quality and quantity trends. The third part concludes the article with a discussion of drinking water case studies in the United States, to give a snapshot of current use and protection trends, highlighting planning tools, best management practices and intervention solutions. Given the current status of water protection laws and policies in the U.S., this discussion of best management practices is targeted towards municipalities, with the aim of linking it to sustainable development policies.